Investigation of optoelectronic properties using single-molecule laser active media - Elzahra, Zainab A.; Aljaberi, Hassan A.; Al-Robayi, Enas M.; Amer, Safa (Opto-Electronics Review, 2025)
Organic molecules with extended π-conjugation frameworks are emerging as promising candidates for active media in nanoscale optoelectronic applications. Benzodichalco-genophene (BDC) derivatives, in particular, exhibit rigid planar geometries and tunable electronic properties, making them attractive for use in single-molecule laser devices. This study theoretically examines the structural, electronic, optical, and charge transport properties of several BDC molecules using advanced computational methods. Geometry optimizations were conducted with the Perdew Burke Ernzerhof (PBE) functional via the SIESTA package, while electronic properties were evaluated at the B3LYP/3-21G level. Time-dependent density functional theory (TD-DFT) was employed to simulate optical absorption spectra, and the GOLLUM code was used to model charge transport through molecular junctions based on non-equilibrium Green’s function formalism. The findings reveal that increasing molecular length narrows the highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) gap, enhances orbital delocalization, and improves electron transmission. Optical simulations revealed red-shifted absorption peaks and increased oscillator strengths, indicating enhanced light-matter interactions. Furthermore, density of states analysis confirmed the transition from HOMO- to LUMO-dominated transport with greater conjugation. Overall, BDC derivatives show strong potential for integration into molecular-scale lasers and optoelectronic devices, paving the way for future experimental and technological advancements.